2019
DOI: 10.1177/0739456x19873382
|View full text |Cite
|
Sign up to set email alerts
|

Explaining Spatial Variations in Residential Energy Usage Intensity in Chicago: The Role of Urban Form and Geomorphometry

Abstract: Understanding the spatial pattern of energy consumption within buildings is essential to urban energy planning and management. This study explores the spatial complexity of residential energy usage intensity, with a focus on urban form and geomorphometry attributes. Using spatial regression models, we find that while vegetation and isolation have more local impact on energy intensity, urban porosity and roughness length have consistent spillover effects on building electricity usage intensity in Chicago. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Our studies proved that 3D form deserves more attention in research on the relationship between urban form and building energy consumption and CO 2 emission [69,70]. Urban 3D form takes into account more comprehensive morphological information.…”
Section: Discussionmentioning
confidence: 62%
“…Our studies proved that 3D form deserves more attention in research on the relationship between urban form and building energy consumption and CO 2 emission [69,70]. Urban 3D form takes into account more comprehensive morphological information.…”
Section: Discussionmentioning
confidence: 62%
“…There are no firm frameworks and well-established schemes for implementation of energy renovation programmes, especially in multi-flat buildings [11][12][13][14][15]19,21,52].…”
Section: Problems With Legal Framework For Renovation Of Residential Buildingsmentioning
confidence: 99%
“…Several important studies [11][12][13] were conducted to analyze the impact of urban form and geomorphometry impact on residential energy consumption. The studies found that neighborhood street configuration and tree shade have significant effect on residential energy consumption and, consequently, greenhouse gas emissions.…”
Section: Introductionmentioning
confidence: 99%
“…The spatial shaping of the underground and aboveground parts of such investments requires the analysis of various design concepts to determine the best spatial solution, in which-apart from satisfying the conditions of applicable legal acts or requirements of current standards, etc.-it is important to obtain the largest possible usable area of the aboveground and underground parts of the new building [48,49]. For these reasons, it is advantageous to develop a numerical model that enables the computational simulation of various options for a building's spatial solution.…”
Section: Introduction 1backgroundmentioning
confidence: 99%